SOCIAL CONDITIONS OF THE SCHEDULED CASTIS: . - Khan, Mumtaz AU . (Journal of Dharma, 1991)
The Scheduled Castes who constitute a sizable proportion cif the population of India (15%) have come to the fore front to-day in all discussions, conferences and seminars. There are two important reasons for this. -First, they were neglected and quite often oppressed for 8 - long time on the ground of untouchability. They were subjected to all forms of social discrimination and hence their status remained the lowest in the Hindu society. However, since independence the state has attempted to improve the status of these people.